Common general surgical never events: analysis of NHS England never event data. (8th March 2021) - Omar, Islam; Singhal, Rishi; Wilson, Michael; Parmar, Chetan; Khan, Omar; Mahawar, Kamal
Abstract: Background: There is little available data on common general surgical never events (NEs). Lack of this information may have affected our attempts to reduce the incidence of these potentially serious clinical incidents. Objectives: The purpose of this study was to identify common general surgical NEs from the data held by the National Health Service (NHS) England. Methods: We analysed the NHS England NE data from April 2012 to February 2020 to identify common general surgical NEs. Results: There was a total of 797 general surgical NEs identified under three main categories such as wrong-site surgery ( n  = 427; 53.58%), retained items post-procedure ( n  = 355; 44.54%) and wrong implant/prosthesis ( n  = 15; 1.88%). We identified a total of 56 common general surgical themes—25 each in the wrong-site surgery and retained foreign body categories and six in wrong implants category. Wrong skin condition surgery was the commonest wrong-site surgery ( n  = 117; 27.4%). There were 18 wrong-side chest drains (4.2%) and 18 (4.2%) wrong-side angioplasty/angiograms. There were seven (1.6%) instances of confusion in pilonidal/perianal/perineal surgeries and six (1.4%) instances of biopsy of the cervix rather than the colon or rectum. Retained surgical swabs were the most common retained items ( n  = 165; 46.5%). There were 28 (7.9%) laparoscopic retrieval bags with or without the specimen, 26 (7.3%) chest drain guide wires, 26 (7.3%) surgical needles and 9 (2.5%) surgical drains. Wrong stents were the most common ( n  = 9; 60%) wrong implants followed by wrong breast implants ( n  = 2; 13.3%). Conclusion: This study found 56 common general surgical NEs. This information is not available to surgeons around the world. Increased awareness of these common themes of NEs may allow for the adoption of more effective and specific safeguards and ultimately help reduce their incidence.